The invention of the sequel : expanding prose fiction in early modern Spain - Hinrichs, William H. (William Hastings) (Colección Támesis. Monografías ;, 2011)
William H. Hinrichs proposes a new way of tracing the history of the early modern Spanish novel through the prism of literary continuation. He identifies and examines the Golden Age narratives that invented the sequel and the narrative genres that the sequel in turn invented.